Enzymolysis modified starch adsorbent and preparation method thereof

The starch liquid is pretreated through gradient temperature-ultrasound collaborative treatment and cold plasma treatment, combined with enzymatic lysis reaction, modified sulfonate sodium alginate cross-linking and concave-convex rod filling, the problem of unsatisfactory adsorption performance and stability of the existing enzymatic modified starch adsorbent is solved, and more efficient adsorption performance and more stable structure are achieved.

CN119869468AActive Publication Date: 2025-04-25GUANGDONG ZHONGQING FENGTAI BIOCHEMICAL TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510329962.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-04-25
Estimated Expiration
2045-03-20

AI Technical Summary

Technical Problem

The adsorption performance and adsorption performance stability of the existing enzymatically modified starch adsorbents are not ideal.

Method used

The starch liquid was pretreated by gradient temperature-ultrasound collaborative treatment, followed by cold plasma treatment and enzymatic reaction under specific conditions, followed by addition of modified sodium sulfonate alginate and epoxychlorohydrin for cross-linking reaction, and the pretreated concave and convex rods were filled in the network structure.

Benefits of technology

It significantly improves the adsorption capacity and adsorption performance stability of starch adsorbents, and enhances its mechanical strength and adsorption capacity to heavy metal ions and organic pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an enzymolysis modified starch adsorbent and a preparation method thereof, and relates to the technical field of adsorbents. Comprising the following steps: adding corn starch into deionized water, carrying out gradient heating-ultrasonic synergistic treatment, carrying out cold plasma treatment on a pretreated starch solution in a nitrogen atmosphere, adjusting the pH value, heating, adding a compound enzyme for enzymolysis, adding modified sulfonic sodium alginate for reaction, adding epoxy chloropropane, and stirring for reaction; and then carrying out cold plasma treatment in a nitrogen atmosphere, adding the pretreated attapulgite, carrying out a stirring reaction, adding ammonium sulfate and acrylamide, discharging air, and after the reaction, carrying out filtering, washing and drying treatment to obtain the enzymolysis modified starch adsorbent. The pretreatment of the corn starch effectively improves the reaction activity of starch particles; due to the introduction of the pretreated attapulgite and other components, the adsorption capacity and the adsorption capacity stability are further improved. Therefore, the adsorbent disclosed by the invention has a wider application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adsorbents, and in particular to an enzymatically modified starch adsorbent and a preparation method thereof. Background Art

[0002] Starch is a natural high molecular compound of polysaccharide formed by the polycondensation of glucose. It is the most abundant renewable material in nature, degradable and will not pollute the environment. There are a large number of reactive hydroxyl groups in its molecular chain, which provides a structural basis for the modification of starch. Modified starch is based on the inherent properties of natural starch. In order to improve the performance of starch and expand its application range, physical, chemical or enzymatic treatment is used to introduce new functional groups on starch molecules or change the size of starch molecules and the properties of starch particles, thereby changing the natural properties of starch and making it more suitable for certain application requirements. As an adsorbent, modified starch is widely used in food, medicine, agriculture, environmental protection and other fields due to its safety, non-toxicity and good biodegradability.

[0003] Porous starch is a natural biosorbent. Currently, amylase enzymatic hydrolysis is often used to form many microporous structures on the surface of starch particles, which helps to increase the specific surface area and pore volume of starch, thereby improving the adsorption capacity of starch. However, the enzymatic method will cause porous starch to have defects such as small specific surface area, small pore volume, shallow pore depth, poor particle firmness, and easy breakage. These problems seriously affect the adsorption effect and practical application of porous starch. In order to solve this technical problem, patent technology document CN105642244B proposes a preparation method of a cross-linked-enzymatic composite ultrafine modified starch adsorbent, comprising the following steps: (1) using an ultrafine grinder to ultrafinely grind corn, sweet potato, and potato starch into ultrafine starch with a particle size of 10-50μm; (2) mixing the three ultrafine starches in a mass ratio of 1:4:3 and adding them into water and stirring to obtain a starch emulsion; (3) adjusting the pH of the starch emulsion to 7.5-8.5, and adding a A quantitative sodium tripolyphosphate solution is cross-linked at 75-80°C for 1-1.5 hours; (4) the cross-linked starch emulsion is centrifuged and dehydrated, washed with deionized water and freeze-dried; (5) the cross-linked starch is watered and adjusted to starch emulsion again, the pH is adjusted to 6.5-7.5, and then α-amylase and isoamylase are added to react at 50°C for 12-15 hours; (6) the enzymatically hydrolyzed starch emulsion is centrifuged, washed, dried, and passed through a 40-100 mesh sieve to obtain a cross-linked-enzymatically hydrolyzed composite ultrafine modified starch. The modified starch of the invention significantly increases the specific surface area and mechanical strength of porous starch, and improves the adsorption capacity of porous starch to harmful components, especially heavy metal elements.

[0004] However, the adsorption performance and adsorption performance stability of the enzymatically modified starch adsorbents prepared by these existing solutions still need to be improved. Summary of the invention

[0005] The purpose of the present invention is to provide an enzymatically modified starch adsorbent and a preparation method thereof, to solve the following technical problems: The existing enzymatically modified starch adsorbents still have problems with unsatisfactory adsorption performance and adsorption performance stability.

[0006] The purpose of the present invention can be achieved by the following technical solutions: A method for preparing an enzymatically modified starch adsorbent comprises the following steps: Step S1: adding corn starch to deionized water, and then performing gradient temperature increase-ultrasound synergistic treatment to obtain a pretreated starch solution; Step S2: Under a nitrogen atmosphere, the pretreated starch solution is subjected to cold plasma treatment, and then the pH is adjusted to 5-6, the temperature is raised to 40-50° C., a composite enzyme is added, and enzymolysis is performed at 40-50° C. for 20-25 hours, and an enzymolyzed starch solution is obtained after high temperature treatment; Step S3: adding modified sodium sulfonate alginate to the enzymatic starch solution, stirring and reacting at 35-40° C. for 1.5-2 hours, then adding epichlorohydrin and stirring and reacting for 2.5-3 hours to obtain a pre-cross-linked starch solution; Step S4: Under a nitrogen atmosphere, the pre-cross-linked starch solution is treated with cold plasma, and then the pre-treated attapulgite is added and stirred for 0.8-1h, and then ammonium sulfate and acrylamide are added and the air is exhausted, and the reaction is carried out at 55-60°C for 3-4h, and then filtered, washed and dried to obtain an enzymatically modified starch adsorbent.

[0007] Preferably, the usage ratio of deionized water and corn starch in step S1 is 100-120 mL: 30-35 g; The gradient heating-ultrasonic synergistic treatment in step S1 is firstly carried out at 20-30°C with a power of 280-300 W, a frequency of 35-40 kHz, and a duration of 10-15 min for the first ultrasonic treatment, and then at 65-66°C with a power of 280-300 W, a frequency of 30-40 kHz, and a duration of 8-10 min for the second ultrasonic treatment.

[0008] Preferably, the gas flow rate during the cold plasma treatment in step S2 is 8-10 L / min, the power is 200-300 W, the voltage is 50-100 V, and the total treatment time is 6-10 min; The dosage ratio of the pretreated starch solution and the complex enzyme in step S2 is 130-155 g: 0.295-0.345 g; The complex enzyme in step S2 is obtained by mixing α-amylase and saccharifying enzyme; The temperature of the high temperature treatment in step S2 is 80-90° C., and the treatment time is 10-20 minutes.

[0009] Preferably, the compound enzyme is composed of α-amylase and saccharifying enzyme in a ratio of 0.075-0.085 g: 0.22-0.26 g.

[0010] Preferably, the dosage ratio of the enzymatic starch solution, modified sodium sulfonate alginate and epichlorohydrin in step S3 is 130-155 g: 4-5 g: 1-2 mL.

[0011] Preferably, the preparation method of the modified sulfonic acid sodium alginate in step S3 is as follows: Sodium alginate is added to deionized water, stirred at 200-300 r / min for 1-2 hours at 50-60°C, then aminosulfonic acid is added, stirred evenly, the pH is adjusted to 8-9 with sodium hydroxide solution and stirred for 3-4 hours, cooled to 20-30°C, ethanol is added, stirred evenly, filtered, washed and dried to obtain modified sulfonic acid sodium alginate.

[0012] Preferably, the usage ratio of deionized water, sodium alginate, aminosulfonic acid and ethanol is 200mL: 5-10g: 2.4-7.3g: 200-400mL; The concentration of the sodium hydroxide solution is 0.1 mol / L.

[0013] Preferably, the gas flow rate during the cold plasma treatment in step S4 is 8-10 L / min, the power is 200-300 W, the voltage is 50-100 V, and the total treatment time is 8-10 min; In step S4, the usage ratio of the pre-cross-linked starch solution, the pre-treated attapulgite, ammonium sulfate and acrylamide is 135-162 g: 2.5-3 g: 0.2-0.3 g: 8-10 g.

[0014] Preferably, the preparation method of the pretreated attapulgite in step S4 is as follows: Add attapulgite to the hydrochloric acid solution, then stir at 300-400 r / min for 12-15 hours at 60-80° C., filter and dry to obtain the pretreated attapulgite.

[0015] Preferably, the usage ratio of the hydrochloric acid solution and the attapulgite is 100-150 mL: 5-8 g; The concentration of the hydrochloric acid solution is 1 mol / L.

[0016] As a further embodiment of the present invention.

[0017] Beneficial effects of the present invention: The present invention provides an enzymatically modified starch adsorbent and a preparation method thereof. The present invention effectively improves the adsorption capacity and adsorption capacity stability of the starch adsorbent through the following method.

[0018] (1) During the preparation of the pretreated starch solution, the first ultrasonic treatment changes the surface microstructure of the starch particles, reducing the particle size and increasing the specific surface area, providing more contact sites for subsequent reactions with other reagents, which is beneficial to the combination of enzymes and starch molecules during enzymatic hydrolysis. The specific temperature and ultrasound synergistic effect during the second ultrasonic treatment can further destroy the hydrogen bonds and other forces inside the starch molecules, causing the molecular chains to stretch to a certain extent, further increasing the reactivity of the starch, thereby accelerating the enzymatic hydrolysis reaction rate and making the enzymatic hydrolysis more complete. Ultimately, the adsorbent can form a more complex, uniform, and porous network structure after subsequent grafting copolymerization and other reactions.

[0019] (2) Cold plasma treatment under specific conditions during the preparation of enzymatic starch solution will make the surface of starch particles rough, forming many tiny grooves and pores, and will also increase the number of active sites and functional groups on the surface, thereby significantly increasing the specific surface area of ​​starch and the contact area between starch molecules and enzymes, making some chemical bonds on starch molecules easier to be recognized and broken by enzymes; at the same time, some nitrogen-containing active groups will be introduced on the surface of starch molecules to enhance the binding force between the adsorbent and pollutants. Combined with the full enzymatic hydrolysis of α-amylase and saccharifying enzyme compounded in a specific ratio under specific conditions, the starch molecules will form a more stable structure. Therefore, this process further improves the adsorption capacity and adsorption capacity stability of the adsorbent.

[0020] (3) The sulfonic acid groups in the modified sulfonic acid sodium alginate of the present invention can interact with the hydroxyl groups and other groups in the enzymatic starch solution. When epichlorohydrin is subsequently added for cross-linking reaction, these interactions can promote the formation of a more complex, more uniform and more stable cross-linked network structure. This cross-linked network structure not only enhances the stability of the adsorbent, enabling it to maintain good adsorption performance under different environmental conditions, but also improves the mechanical strength of the adsorbent and reduces the breakage and loss of the adsorbent during use. At the same time, since sodium alginate itself has a certain hydrophilicity, it is combined with the hydrophilicity of the sulfonic acid group, so that the modified sulfonic acid sodium alginate can contact and interact with pollutant molecules faster, thereby accelerating the adsorption rate.

[0021] (4) The attapulgite has a special crystal structure and a large specific surface area. The present invention fills the pretreated attapulgite into the network structure of the enzymatically modified starch, which can provide more adsorption sites for the enzymatically modified starch adsorbent, enhance the ion exchangeability of the adsorbent, and support and reinforce the network structure, so that it can be more stably combined with more adsorbed substances; at the same time, the attapulgite can adsorb a part of the substance through physical adsorption, while the enzymatically modified starch can react chemically with the adsorbed substance or produce a complexation through its own active groups. The combination of the two can further enhance the overall adsorption performance of the adsorbent.

[0022] Therefore, the modified starch adsorbent prepared by the present invention has more excellent adsorption performance, adsorption performance stability, and broad application prospects. DETAILED DESCRIPTION

[0023] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] The properties and sources of some raw materials in the present invention are as follows: α-Amylase (BAN 480L) was purchased from Novozymes China Biotechnology Co., Ltd.; saccharifying enzyme (AMG 300L) was purchased from Novozymes China Biotechnology Co., Ltd.; attapulgite was purchased from Hubei Yongkuo Technology Co., Ltd., CAS: 12174-11-7.

[0025] Example 1: A method for preparing an enzymatically modified starch adsorbent is as follows: S1: 30 g corn starch was added to 100 mL deionized water, and the solution was firstly subjected to an ultrasonic treatment at 20°C with a power of 280 W, a frequency of 35 kHz, and a duration of 10 min, and then subjected to a secondary ultrasonic treatment at 65°C with a power of 280 W, a frequency of 30 kHz, and a duration of 8 min to obtain a pretreated starch solution; S2: Under nitrogen atmosphere, 130 g of pretreated starch solution was treated with cold plasma at a gas flow rate of 8 L / min, a power of 200 W, a voltage of 50 V, and a total treatment time of 6 min. Then, the pH was adjusted to 5 with a 0.1 mol / L citric acid solution, and after heating to 40°C, 0.075 g of α-amylase and 0.22 g of saccharifying enzyme were added, and enzymolysis was carried out at 40°C for 20 h. Finally, a high-temperature treatment was carried out at 80°C for 10 min to obtain an enzymolyzed starch solution. S3: Add 5 g of sodium alginate to 200 mL of deionized water, stir at 200 r / min for 1 h at 50 ° C, then slowly add 2.4 g of aminosulfonic acid, stir evenly, add 0.1 mol / L sodium hydroxide solution to adjust the pH value to 8 and stir for 3 h, cool to 20 ° C and slowly add 200 mL of ethanol, stir evenly, collect the precipitate by suction filtration and wash the precipitate with ethanol 3 times, and finally dry at 40-50 ° C to obtain modified sulfonic acid sodium alginate; S4: Add 4 g of modified sulfonic acid sodium alginate to 130 g of enzymatic starch solution, stir and react at 35° C. for 1.5 h, then add 1 mL of epichlorohydrin and stir and react at 35° C. for 2.5 h to obtain a pre-cross-linked starch solution; S5: adding 5 g of attapulgite to 100 mL of 1 mol / L hydrochloric acid solution, stirring at 300 r / min for 12 h at 60° C., filtering, and drying to obtain pretreated attapulgite; S6: Under a nitrogen atmosphere, 135 g of pre-cross-linked starch liquid was treated with cold plasma at a gas flow rate of 8 L / min, a power of 200 W, a voltage of 50 V, and a total treatment time of 8 min. Then, 2.5 g of pretreated attapulgite was added and stirred for 0.8 h. Then, 0.2 g of ammonium sulfate and 8 g of acrylamide were added. Nitrogen was introduced to exclude air. The mixture was reacted at 55 °C for 3 h. The mixture was filtered and the precipitate was washed 3 times with deionized water. Finally, the mixture was dried at 55 °C to obtain an enzymatically modified starch adsorbent.

[0026] Example 2: A method for preparing an enzymatically modified starch adsorbent is as follows: S1: 33 g corn starch was added to 110 mL deionized water, and the mixture was firstly ultrasonically treated at 25°C with a power of 290 W, a frequency of 38 kHz, and a duration of 13 min, and then the mixture was ultrasonically treated at 65.5°C with a power of 290 W, a frequency of 35 kHz, and a duration of 9 min to obtain a pretreated starch solution; S2: Under nitrogen atmosphere, 143 g of pretreated starch solution was treated with cold plasma at a gas flow rate of 9 L / min, a power of 250 W, a voltage of 80 V, and a total treatment time of 8 min. Then, the pH was adjusted to 5.5 with 0.1 mol / L citric acid solution, and 0.08 g of α-amylase and 0.24 g of saccharifying enzyme were added after heating to 45 °C, and enzymolysis was carried out at 45 °C for 23 h. Finally, high-temperature treatment was carried out at 85 °C for 15 min to obtain enzymolyzed starch solution. S3: Add 8 g of sodium alginate to 200 mL of deionized water, stir at 250 r / min for 1.5 h at 55 ° C, then slowly add 4.85 g of aminosulfonic acid, stir evenly, add 0.1 mol / L sodium hydroxide solution to adjust the pH value to 8.5 and stir for 3.5 h, cool to 25 ° C, slowly add 300 mL of ethanol, stir evenly, collect the precipitate by suction filtration, wash the precipitate with ethanol 4 times, and finally dry at 45 ° C to obtain modified sulfonic acid sodium alginate; S4: Add 4.5 g of modified sulfonic acid sodium alginate to 143 g of enzymatic starch solution, stir and react at 38° C. for 1.8 h, then add 1.5 mL of epichlorohydrin and stir and react at 38° C. for 2.8 h to obtain a pre-cross-linked starch solution; S5: adding 7 g of attapulgite to 130 mL of 1 mol / L hydrochloric acid solution, stirring at 70° C. and 350 r / min for 14 h, filtering, and drying to obtain pretreated attapulgite; S6: Under a nitrogen atmosphere, 149 g of pre-cross-linked starch liquid was treated with cold plasma at a gas flow rate of 9 L / min, a power of 250 W, a voltage of 80 V, and a total treatment time of 9 min. Then, 2.8 g of pretreated attapulgite was added and stirred for 0.9 h. Then, 0.25 g of ammonium sulfate and 9 g of acrylamide were added. Nitrogen was introduced to exclude air. The mixture was reacted at 58°C for 3.5 h. The mixture was filtered and the precipitate was washed 4 times with deionized water. Finally, the mixture was dried at 58°C to obtain an enzymatically modified starch adsorbent.

[0027] Example 3: A method for preparing an enzymatically modified starch adsorbent is as follows: S1: 35 g corn starch was added to 120 mL deionized water, and the solution was firstly ultrasonically treated at 30°C with a power of 300 W, a frequency of 40 kHz, and a duration of 15 min, and then the solution was ultrasonically treated at 66°C with a power of 300 W, a frequency of 40 kHz, and a duration of 10 min to obtain a pretreated starch solution; S2: Under nitrogen atmosphere, 155 g of pretreated starch solution was treated with cold plasma at a gas flow rate of 10 L / min, a power of 300 W, a voltage of 100 V, and a total treatment time of 10 min. Then, the pH was adjusted to 6 with a 0.1 mol / L citric acid solution, and after heating to 50°C, 0.085 g of α-amylase and 0.26 g of saccharifying enzyme were added, and enzymolysis was performed at 50°C for 25 h. Finally, a high-temperature treatment was performed at 90°C for 20 min to obtain an enzymolyzed starch solution. S3: Add 10 g of sodium alginate to 200 mL of deionized water, stir at 300 r / min for 2 h at 60 ° C, then slowly add 7.3 g of aminosulfonic acid, stir evenly, add 0.1 mol / L sodium hydroxide solution to adjust the pH value to 9 and stir for 4 h, cool to 30 ° C, slowly add 400 mL of ethanol, stir evenly, collect the precipitate by suction filtration, wash the precipitate with ethanol 5 times, and finally dry at 50 ° C to obtain modified sulfonic acid sodium alginate; S4: Add 5 g of modified sulfonic acid sodium alginate to 155 g of enzymatic starch solution, stir and react at 40° C. for 2 h, then add 2 mL of epichlorohydrin and stir and react at 40° C. for 3 h to obtain a pre-cross-linked starch solution; S5: adding 8 g of attapulgite to 150 mL of a 1 mol / L hydrochloric acid solution, stirring at 400 r / min for 15 h at 80° C., filtering, and drying to obtain a pretreated attapulgite; S6: Under a nitrogen atmosphere, 162 g of pre-cross-linked starch liquid was treated with cold plasma at a gas flow rate of 10 L / min, a power of 300 W, a voltage of 100 V, and a total treatment time of 10 min. Then, 3 g of pretreated attapulgite was added and stirred for 1 h. Then, 0.3 g of ammonium sulfate and 10 g of acrylamide were added. Nitrogen was introduced to exclude air. The mixture was reacted at 60 °C for 4 h. The mixture was filtered and the precipitate was washed with deionized water for 5 times. Finally, the mixture was dried at 60 °C to obtain an enzymatically modified starch adsorbent.

[0028] Comparative Example 1: Compared with Example 1, this comparative example only replaces the "first ultrasonic treatment at 20°C with a power of 280 W, a frequency of 35 kHz, and a duration of 10 min, and then a secondary ultrasonic treatment at 65°C with a power of 280 W, a frequency of 30 kHz, and a duration of 8 min" in the preparation process of the pretreated starch liquid with "ultrasonic treatment at 65°C with a power of 280 W, a frequency of 30 kHz, and a duration of 18 min", and the remaining steps and parameters are the same, and this comparative example will not be repeated, and finally an enzymatic modified starch adsorbent is obtained.

[0029] Comparative Example 2: Compared with Example 1, this comparative example only replaces the "first ultrasonic treatment at 20°C with a power of 280 W, a frequency of 35 kHz, and a duration of 10 min, and then a secondary ultrasonic treatment at 65°C with a power of 280 W, a frequency of 30 kHz, and a duration of 8 min" in the preparation process of the pretreated starch liquid with "stirring treatment at 300 r / min for 18 min at 65°C", and the remaining steps and parameters are the same, and will not be repeated in this comparative example, and finally an enzymatic modified starch adsorbent is obtained.

[0030] Comparative Example 3: Compared with Example 1, this comparative example only does not perform cold plasma treatment during the preparation of the enzymatic starch solution, and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally an enzymatic modified starch adsorbent is obtained.

[0031] Comparative Example 4: Compared with Example 1, this comparative example only replaces the "0.075g of α-amylase and 0.22g of saccharifying enzyme" added in the preparation process of the enzymatic starch solution with "0.295g of α-amylase", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally an enzymatic modified starch adsorbent is obtained.

[0032] Comparative Example 5: Compared with Example 1, this comparative example only replaces the "0.075g of α-amylase and 0.22g of saccharifying enzyme" added in the preparation process of the enzymatic starch solution with "0.295g of saccharifying enzyme", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally an enzymatic modified starch adsorbent is obtained.

[0033] Comparative Example 6: Compared with Example 1, this comparative example only replaces the "modified sodium sulfonate alginate" added in the preparation process of the pre-cross-linked starch solution with "sodium alginate", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally an enzymatically modified starch adsorbent is obtained.

[0034] Comparative Example 7: Compared with Example 1, this comparative example only replaces the "modified sodium sulfonate alginate" added in the preparation process of the pre-cross-linked starch solution with the "pretreated attapulgite" prepared by S5 in Example 1 of the present invention, and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally an enzymatic modified starch adsorbent is obtained; Comparative Example 8: Compared with Example 1, this comparative example only replaces the "pretreated attapulgite" added in the preparation process of the enzymatically modified starch adsorbent in S6 with "attapulgite", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally the enzymatically modified starch adsorbent is obtained.

[0035] Comparative Example 9: Compared with Example 1, this comparative example only replaces the "pretreated attapulgite" added in the process of enzymatically modified starch adsorbent in S6 with the "modified sodium sulfonate alginate" prepared in S3 of Example 1 of the present invention, and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally obtains an enzymatically modified starch adsorbent; Comparative Example 10: Compared with Example 1, this comparative example only does not perform cold plasma treatment during the preparation process of the enzymatically modified starch adsorbent in S6, and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally the enzymatically modified starch adsorbent is obtained.

[0036] Performance testing: Adsorption capacity test at 25°C: Weigh 0.05g of enzymatically modified starch adsorbent sample and soak it in 50mL of organic (cationic yellow) solution with a concentration of 500mg / L and oscillate at constant temperature at 25℃ for 2h. Then use a visible spectrophotometer to measure the concentration of cationic yellow in the solution and calculate the corresponding adsorption amount (mg / g). 2+ , Pb 2+ , Hg 2+ 、Ni 2+) 0.05g of the enzymatically modified starch adsorbent sample was added to 50mL of a heavy metal ion solution with a concentration of 500mg / L, and the mixture was oscillated at a constant temperature of 25°C for 2h in a constant temperature oscillation box. The concentration of heavy metal ions in each solution was then determined using an atomic absorption spectrophotometer, and the corresponding adsorption amount (mg / g) was calculated. The adsorption capacity (mg / g) of the enzymatically modified starch adsorbent prepared in Examples 1 to 3 and Comparative Examples 1 to 10 was determined according to this method, and the test results are shown in Table 1.

[0037] Test of adsorption capacity at 50°C: Weigh 0.05g of enzymatically modified starch adsorbent sample and soak it in 50mL of 500mg / L organic (cationic yellow) solution and oscillate at 50℃ for 2h. Then use a visible spectrophotometer to measure the concentration of cationic yellow in the solution and calculate the corresponding adsorption amount (mg / g). 2+ , Pb 2+ , Hg 2+ 、Ni 2+ For one of the simulated wastewater solutions, 0.05g of the enzymatically modified starch adsorbent sample was added to 50mL of a heavy metal ion solution with a concentration of 500mg / L, and the solution was oscillated at a constant temperature of 50°C for 2h in a constant temperature oscillation box. The concentration of heavy metal ions in each solution was then determined using an atomic absorption spectrophotometer, and the corresponding adsorption amount (mg / g) was calculated. The adsorption capacity (mg / g) of the enzymatically modified starch adsorbents prepared in Examples 1 to 3 and Comparative Examples 1 to 10 was determined according to this method, and the test results are shown in Table 1 below.

[0038] Table 1: Performance test results of Examples 1 to 3 and Comparative Examples 1 to 10

[0039] Data Analysis: It can be seen from Table 1 that the enzymatically modified starch adsorbent prepared by the present invention has better adsorption capacity for organic pollutants and heavy metal ions, as well as adsorption capacity stability.

[0040] This may be due to: (1) During the preparation of starch pretreatment, the mechanical effect and cavitation effect of the first ultrasonic treatment will cause microstructural changes such as microcracks and grooves on the surface of starch particles, reduce the particle size, and increase the specific surface area; this provides more contact sites for subsequent reactions with other reagents, which is beneficial to the combination of enzymes and starch molecules during enzymatic hydrolysis. The specific temperature and ultrasonic synergy during the second ultrasonic treatment can further destroy the hydrogen bonds and other forces inside the starch molecules, and the molecular chains will stretch to a certain extent, further increasing the reaction activity of starch, thereby accelerating the enzymatic hydrolysis reaction rate and making the enzymatic hydrolysis more complete. Ultimately, the adsorbent forms a more complex, uniform, and porous network structure after subsequent grafting copolymerization reactions, thereby improving the adsorption capacity and adsorption stability of heavy metal ions, organic pollutants, etc.

[0041] (2) Cold plasma treatment under specific conditions during the preparation of enzymatic starch solution will make the surface of starch particles rough, forming many tiny grooves and pores, and will also increase the number of active sites and functional groups on the surface, thereby significantly increasing the specific surface area of ​​starch and the contact area between starch molecules and enzymes, making some chemical bonds on starch molecules easier to be recognized and broken by enzymes; at the same time, some nitrogen-containing active groups will be introduced on the surface of starch molecules to enhance the binding force between the adsorbent and pollutants. Combined with the full enzymatic hydrolysis of α-amylase and saccharifying enzyme compounded in a specific ratio under specific conditions, the starch molecules will form a more stable structure. Therefore, this process further improves the adsorption capacity and adsorption capacity stability of the adsorbent.

[0042] (3) The sulfonic acid groups in the modified sulfonic acid sodium alginate of the present invention can interact with the hydroxyl groups and other groups in the enzymatic starch solution. When epichlorohydrin is subsequently added for cross-linking reaction, these interactions can promote the formation of a more complex, more uniform and more stable cross-linked network structure. This cross-linked network structure not only enhances the stability of the adsorbent, enabling it to maintain good adsorption performance under different environmental conditions, but also improves the mechanical strength of the adsorbent and reduces the breakage and loss of the adsorbent during use. At the same time, since sodium alginate itself has a certain hydrophilicity, it is combined with the hydrophilicity of the sulfonic acid group, so that the modified sulfonic acid sodium alginate can contact and interact with pollutant molecules faster, thereby accelerating the adsorption rate.

[0043] (4) The attapulgite has a special crystal structure and a large specific surface area. The present invention fills the pretreated attapulgite into the network structure of the enzymatically modified starch to provide more adsorption sites for the enzymatically modified starch adsorbent, enhance the ion exchangeability of the adsorbent, and support and reinforce the network structure, so that it can combine with more adsorbed substances more stably; at the same time, the attapulgite can adsorb a part of the substance through physical adsorption, while the enzymatically modified starch can react chemically with the adsorbed substance or produce a complexation through its own active groups. The combination of the two further enhances the overall adsorption performance of the adsorbent.

[0044] (5) Cold plasma treatment of pre-crosslinked starch liquid under specific conditions can improve its pore structure and introduce more active groups or defects, thereby increasing the specific surface area and adsorption sites of the enzymatically modified starch adsorbent; at the same time, it can also promote the further crosslinking reaction of the unreacted groups in the pre-crosslinked starch liquid and promote the change of the crosslinking structure, so that the connection between the molecular chains is tighter, forming a more stable and regular three-dimensional network structure. Therefore, the enzymatically modified starch adsorbent prepared by the present invention has better adsorption capacity and adsorption capacity stability.

[0045] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing an enzymatically modified starch adsorbent, characterized in that: The following steps are involved: Step S1: adding corn starch to deionized water, and then performing gradient temperature increase-ultrasound synergistic treatment to obtain a pretreated starch solution; Step S2: Under a nitrogen atmosphere, the pretreated starch solution is subjected to cold plasma treatment, and then the pH is adjusted to 5-6, the temperature is raised to 40-50° C., a composite enzyme is added, and enzymolysis is performed at 40-50° C. for 20-25 hours, and an enzymolyzed starch solution is obtained after high temperature treatment; Step S3: adding modified sodium sulfonate alginate to the enzymatic starch solution, stirring and reacting at 35-40° C. for 1.5-2 hours, then adding epichlorohydrin and stirring and reacting for 2.5-3 hours to obtain a pre-cross-linked starch solution; Step S4: Under a nitrogen atmosphere, the pre-cross-linked starch solution is treated with cold plasma, and then the pre-treated attapulgite is added and stirred for 0.8-1h, and then ammonium sulfate and acrylamide are added and the air is exhausted, and the reaction is carried out at 55-60°C for 3-4h, and then filtered, washed and dried to obtain an enzymatically modified starch adsorbent.

2. The method for preparing the enzymatically modified starch adsorbent according to claim 1, characterized in that: The usage ratio of deionized water and corn starch in step S1 is 100-120 mL: 30-35 g; The gradient heating-ultrasonic synergistic treatment in step S1 is firstly carried out at 20-30°C with a power of 280-300 W, a frequency of 35-40 kHz, and a duration of 10-15 min for the first ultrasonic treatment, and then at 65-66°C with a power of 280-300 W, a frequency of 30-40 kHz, and a duration of 8-10 min for the second ultrasonic treatment.

3. The method for preparing the enzymatically modified starch adsorbent according to claim 1, characterized in that: The gas flow rate during the cold plasma treatment in step S2 is 8-10 L / min, the power is 200-300 W, the voltage is 50-100 V, and the total treatment time is 6-10 min; The dosage ratio of the pretreated starch solution and the complex enzyme in step S2 is 130-155 g: 0.295-0.345 g; The complex enzyme in step S2 is obtained by mixing α-amylase and saccharifying enzyme; The temperature of the high temperature treatment in step S2 is 80-90° C., and the treatment time is 10-20 minutes.

4. The method for preparing the enzymatically modified starch adsorbent according to claim 3, characterized in that: The compound enzyme is composed of alpha-amylase and saccharifying enzyme in a dosage ratio of 0.075-0.085 g: 0.22-0.26 g.

5. The method for preparing the enzymatically modified starch adsorbent according to claim 1, characterized in that: The dosage ratio of the enzymatic starch solution, modified sodium sulfonate alginate and epichlorohydrin in step S3 is 130-155 g: 4-5 g: 1-2 mL.

6. The method for preparing the enzymatically modified starch adsorbent according to claim 1, characterized in that: The preparation method of the modified sulfonic acid sodium alginate in step S3 is as follows: Sodium alginate is added to deionized water, stirred at 200-300 r / min for 1-2 hours at 50-60°C, then aminosulfonic acid is added, stirred evenly, the pH is adjusted to 8-9 with sodium hydroxide solution and stirred for 3-4 hours, cooled to 20-30°C, ethanol is added, stirred evenly, filtered, washed and dried to obtain modified sulfonic acid sodium alginate.

7. The method for preparing the enzymatically modified starch adsorbent according to claim 6, characterized in that: The usage ratio of deionized water, sodium alginate, aminosulfonic acid and ethanol is 200mL: 5-10g: 2.4-7.3g: 200-400mL; The concentration of the sodium hydroxide solution is 0.1 mol / L.

8. The method for preparing the enzymatically modified starch adsorbent according to claim 1, characterized in that: The gas flow rate during the cold plasma treatment in step S4 is 8-10 L / min, the power is 200-300 W, the voltage is 50-100 V, and the total treatment time is 8-10 min; In step S4, the usage ratio of the pre-cross-linked starch solution, the pre-treated attapulgite, ammonium sulfate and acrylamide is 135-162 g: 2.5-3 g: 0.2-0.3 g: 8-10 g.

9. The method for preparing the enzymatically modified starch adsorbent according to claim 1, characterized in that: The preparation method of the pretreated attapulgite in step S4 is as follows: Add attapulgite to the hydrochloric acid solution, then stir at 300-400 r / min for 12-15 hours at 60-80° C., filter and dry to obtain the pretreated attapulgite.

10. The method for preparing the enzymatically modified starch adsorbent according to claim 9, characterized in that: The usage ratio of the hydrochloric acid solution and the attapulgite is 100-150 mL: 5-8 g; The concentration of the hydrochloric acid solution is 1 mol / L.

Citation Information

Patent Citations

  • Preparation method and application of a cross-linking-enzymolysis composite ultrafine modified starch adsorbent

    CN105642244B

  • Papermaking wastewater treatment agent and manufacturing method thereof

    CN105060444A

  • Preparation method and application of crosslinking-enzymolysis composite superfine modified starch adsorbent

    CN105642244A

  • Kitchen greasy dirt adsorbent and preparation method thereof

    CN106925218A

  • Preparation method of corn porous starch

    CN108018322A